METHODOLOGY FOR TEACHING NANOTECHNOLOGY AND PHOTOVOLTAICS IN HIGHER EDUCATION - Eshboltayev Iqbol Mamirjonovich,; G‘ofurov Saidkamol Zokirjon ogli,; Eshboltayev Ikromjon Iqbol ogli 3, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract This paper is devoted to modern methodological issues in teaching nanotechnology and photovoltaics (the technology of converting solar energy into electrical energy) in higher  education  institutions.  Since  these  fields  are  among  the  key  directions  of technological  progress  and  sustainable  development,  it  is  of  great  importance  to integrate  theoretical  knowledge  with  practical  skills,  apply  interdisciplinary approaches, and develop students’ innovative thinking abilities in the teaching process. The paper analyzes the current state of teaching nanotechnology and photovoltaics, existing challenges, advanced international experiences, and methodological proposals aimed at improving the effectiveness of instruction in these fields. The research results are focused on enriching higher education curricula with new technologies and modern teaching methods.